Which resources help young people to prevent and overcome mental distress in deprived urban areas in Latin America? A protocol for a prospective cohort study (2021)
Introduction Improving the mental health of young people is a global public health priority. In Latin America, young people living in deprived urban areas face various risk factors for mental distress. However, most either do not develop mental distress in the form of depression and anxiety, or recover within a year without treatment from mental health services. This research programme seeks to identify the personal and social resources that help young people to prevent and recover from mental distress. Methods and analysis A cross-sectional study will compare personal and social resources used by 1020 young people (aged 15–16 and 20–24 years) with symptoms of depression and/or anxiety and 1020 without. A longitudinal cohort study will follow-up young people with mental distress after 6 months and 1 year and compare resource use in those who do and do not recover. An experience sampling method study will intensively assess activities, experiences and mental distress in subgroups over short time periods. Finally, we will develop case studies highlighting existing initiatives that effectively support young people to prevent and recover from mental distress. The analysis will assess differences between young people with and without distress at baseline using t-tests and χ2 tests. Within the groups with mental distress, multivariate logistic regression analyses using a random effects model will assess the relationship between predictor variables and recovery. Ethics and dissemination Ethics approvals are received from Ethics Committee in Biomedical Research, Faculty of Medicine, University of Buenos Aires; Faculty of Medicine-Research and Ethics Committee of the Pontificia Universidad Javeriana, Bogotá; Institutional Ethics Committee of Research of the Universidad Peruana Cayetano Heredia and Queen Mary Ethics of Research Committee. Dissemination will include arts-based methods and target different audiences such as national stakeholders, researchers from different disciplines and the general public.